Comparison between results of trabeculectomy in primary congenital glaucoma with and without the use of mitomycin C - Rodrigues, Adriana Maria [UNIFESP] (2004)
Purpose: To evaluate the results of trabeculectomy with and without the use of mitomycin C in children with primary congenital glaucoma.Methods: the authors retrospectively studied the data of 91 patients who underwent the first trabeculectomy for primary congenital glaucoma, with 19 years of follow-up. Success criteria were set with two distinct values of intraocular pressure: lower or equal to 15 mm Hg or lower than 21 mm Hg and separately analyzed.Results: Among the studied patients, 61 had undergone trabeculectomy without mitomycin C and 30 with mitomycin C. the comparison between the groups of patients showed age homogeneity (P = 0.152) and did not demonstrate any difference in preoperative (P = 0.234) and postoperative (P = 0.907) intraocular pressure. Success rates through time, for both pressure limits was not different between the groups. Both age and the presence of previous trabeculotomy did not influence the success of trabeculectomy through time, for the two pressure limits considered. the complication rate was higher among the patients who received mitomycin C (P = 0.010).Conclusions: the success of trabeculectomy for primary congenital glaucoma with mitomycin C was not different than that of trabeculectomy with mitomycin C in the studied patients. Mitomycin C was associated with a higher incidence of complications.